100‐million‐year‐old ant–conifer associates inside French amber: a fortuitous or ecological association?. (12th March 2020) - Moreau, Jean‐David; Perrichot, Vincent; Neraudeau, Didier; Tafforeau, Paul
Abstract : Ants exhibit a plethora of ecological interactions with terrestrial plants. These interactions are broadly surveyed in modern ecosystems, but are much more difficult to unveil in the fossil record. Here, we report a unique ant–conifer association preserved in an opaque piece of 100‐million‐year‐old amber from Charentes in Western France, revealed by propagation phase‐contrast X‐ray synchrotron microtomography (PPC‐SRμCT). Most legs of the ant encircle the conifer twig, and the arthropod harbours a hooked position onto the leafy axis. The conifer is assigned to Glenrosa carentonensis Moreau, Néraudeau, Tafforeau and Dépré, whereas the ant is ascribed to Gerontoformica occidentalis Perrichot, Nel, Néraudeau, Lacau and Guyot. The purpose of this study was to discuss diverse hypotheses that could explain the natural association of these fossils (including random and ecological associations) and its palaeoecological implications. While a mutualistic interaction between Gerontoformica and Glenrosa cannot be unambiguously demonstrated here, these associates raise questions on the ant–conifer interactions during the early ant evolution.